The Future of Drug Monitoring: Integrating Advanced Bioanalytical Techniques into Healthcare - Ashok Kumar, B. S; Disha, N. S.; Khalid, Mohammed (Journal of Neonatal Surgery, 2025)
Advances in bioanalytical techniques have revolutionized drug monitoring, enabling more precise and personalized therapeutic interventions. While tried and true methods and basics are super important, they just don't cut it anymore for doctors and patients alike. They just don't have enough finesse, efficiency, or speed to keep up with all the modern needs of healthcare. Clinically speaking, modern medicine wants quick, specific results and others of that ilk. The emergence of next-generation bioanalytical techniques, including advanced chromatographic methods (such as UPLC and LC-MS/MS), high-resolution mass spectrometry (HRMS), spectroscopic innovations (FTIR, Raman, NMR), biosensors, microfluidics, nanotechnology, and AI-driven analytics, has significantly enhanced drug monitoring capabilities. These new innovations detect levels and metabolite biomarkers of medicines super fast and accurately. This helps doctors to offer treatments that really match individual people and do better monitoring of which therapies are working for patients. Being so quick and precise, this lets doctors make fantastic clinical decisions that really benefit patients on an individual level. The integration of these technologies with electronic health records (EHR) allows for seamless monitoring of drug-drug interactions and patient-specific therapeutic adjustments. While they have amazing potential, there are challenges like high costs, complicated processes, regulatory red tape, and they really require skilled people. Furthermore, issues like sample preparation, matrix interferences, and standardization must be addressed to ensure reliable, reproducible results. Looking ahead, integrating approaches using different types of research data is going to be really important. We're also going to see bedside monitoring the equipment doctors use in their work room get smaller and more manageable. Alongside that we'll keep developing and improving software that doctors can use at the front line when they're thinking about prescribing medications in real time and making decisions. That's going to play a huge role in the future evolution of monitoring drugs that people are taking. Using block chain to keep data as solid as a rock comes to have a big advantage too it can supercharge security and keep everyone in the loop for drug monitoring too. This review highlights key advancements, clinical applications, and future trends in next-generation bioanalytical techniques, emphasizing their potential to transform patient care and therapeutic efficacy.